2020
DOI: 10.33309/2638-7719.030102
|View full text |Cite
|
Sign up to set email alerts
|

3,6’-Dithiothalidomide Reduces Tinnitus Phenotype in Two Different Mouse Preclinical Models of Tinnitus

Abstract: Background: Tinnitus is the perception of a sound in the absence of external stimulation. Tinnitus is a common consequence of damage to the auditory periphery, affecting around 5-12% of the population and inducing intolerable discomfort. Today, no treatment exists to cure tinnitus. From an electrophysiology point of view, tinnitus leads to auditory brainstem responses (ABRs) wave modifications and spontaneous activity changes of the primary auditory cortex (PAC) in human and rodents. Moreover, plasma brain-der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In a previous study, an increase in neuroglial activation in the auditory cortex and medial geniculate body was observed in animals with salicylate‐induced tinnitus (Xia et al, 2020). Furthermore, a link between tumour necrosis factor‐alpha (TNF‐α) in the behavioural phenotype associated with tinnitus was found in animal studies (Hwang et al, 2011, 2017; W. Wang et al, 2019; Gonzalez‐Gonzalez, 2020). Evidence has also shown that TNF‐α appears to play a role in the pathogenesis of periodontitis, and an increased serum level of TNF‐α was observed in patients with periodontitis (Gorska et al, 2003; Engebretson et al, 2007; Ding et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study, an increase in neuroglial activation in the auditory cortex and medial geniculate body was observed in animals with salicylate‐induced tinnitus (Xia et al, 2020). Furthermore, a link between tumour necrosis factor‐alpha (TNF‐α) in the behavioural phenotype associated with tinnitus was found in animal studies (Hwang et al, 2011, 2017; W. Wang et al, 2019; Gonzalez‐Gonzalez, 2020). Evidence has also shown that TNF‐α appears to play a role in the pathogenesis of periodontitis, and an increased serum level of TNF‐α was observed in patients with periodontitis (Gorska et al, 2003; Engebretson et al, 2007; Ding et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, inhibition of tissue necrosis factor reduced the tinnitus phenotype in preclinical models (Hwang et al, 2017;Gonzalez-Gonzalez, 2020).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…TNFα expression is also significantly upregulated in the IC or AC of mice with salicylate-induced tinnitus [15,16]. Further, in mice, intra-ventricle infusion of recombinant TNFα resulted in tinnitus behavior and microglia alterations in the AC following noise exposure [17], and genetic knockout of TNFα or blockade of TNFα expression decreased tinnitus-associated behavior [14,18,19]. Finally, intracochlear TNFα infusion resulted in reduced auditory nerve activity and degradation of inner hair cell synapses in guinea pigs, which could be prevented via systemic TNFα blockade [20].…”
Section: Introductionmentioning
confidence: 99%